2017
DOI: 10.1016/j.joa.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Study design of GENERAL (general practitioners and embolism prevention in NVAF patients treated with rivaroxaban: Real‐life evidence): A multicenter prospective cohort study in primary care physicians to investigate the effectiveness and safety of rivaroxaban in Japanese patients with NVAF

Abstract: BackgroundRivaroxaban, a direct oral anticoagulant (DOAC), has become available for stroke prevention in patients with non-valular atrial fibrillation (NVAF). However, little is known about its effectiveness and safety when prescribed by general practitioners in real-life settings.MethodsGENERAL is a multicenter, prospective, non-interventional observational study of patients receiving rivaroxaban for NVAF in daily clinical practice prescribed specifically by general practitioners. The target number of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Similarly, the size of our study populations and the observation period should be considered when interpreting the results. The original GENERAL study was a single-arm observational study, and the sample size was determined based on the results of the previous studies, including from that of the western countries 12 . However, the actual observed events in the GENERAL study were fewer than expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the size of our study populations and the observation period should be considered when interpreting the results. The original GENERAL study was a single-arm observational study, and the sample size was determined based on the results of the previous studies, including from that of the western countries 12 . However, the actual observed events in the GENERAL study were fewer than expected.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted as part of the GENERAL study. The details of the GENERAL study have been reported elsewhere 12 , 13 . In brief, GENERAL was a multicenter prospective observational study involving patients prescribed rivaroxaban for NVAF in daily clinical practice, specifically by ambulatory primary care physicians in Japan (UMIN000019135, NCT02633982).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the actual outcomes of rivaroxaban use in general practice remain unclear as the previous observational studies of this drug in patients with NVAF were mainly conducted by cardiovascular specialists in university and hospital settings. 7-10 Accordingly, we conducted a multicentre, prospective cohort study: the GENeral practitioners and Embolism pRevention in NVAF patients treated with RivAroxaban: real-Life evidence (GENERAL) study (UMIN000019135, NCT02633982), 11 to investigate the effectiveness and safety of rivaroxaban in Japanese patients with NVAF as prescribed by general practitioners. We also investigated the clinical events that occurred in high-risk patients (i.e., those of extreme age or exhibiting cognitive disorder or frailty) in this study.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The study design has been described previously (Figure 1). 11 In brief, the baseline clinical data, including that regarding cognitive dysfunction and frailty, and the follow-up data including concomitant treatment, were collected until September 2018 (maximum of 3 years). CHADS2, CHA2DS2-VASc (ischemic stroke risk), and HAS-BLED (major bleeding) scores were calculated using the baseline clinical data.…”
Section: Study Design and Populationmentioning
confidence: 99%